A MODEL FOR DEVELOPING STUDENTS CHARACTER IN VOCATIONAL HIGH SCHOOLS IN BANTEN - Atep Iman; Iwan Ridwan; Kurniawan Putra Yudha (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
This research aimed to develop and implement an effective character development model for Vocational High School (SMK) students in Banten Province, Indonesia. Recognizing the importance of character alongside technical skills in producing well-rounded graduates, a mixed-methods approach was employed to gather comprehensive data. Qualitative data was obtained through interviews, observations, and document analysis, while quantitative data was collected through student questionnaires. The findings revealed that SMK students value discipline, responsibility, honesty, cooperation, and mutual cooperation. However, current character development programs in schools are often fragmented and not fully integrated into daily learning. To address this, a three-component character development model was designed: 1) integrating character values into the curriculum, 2) strengthening extracurricular programs, and 3) providing personalized student support. Implementation of the model demonstrated positive outcomes, including improved student knowledge, attitudes, and behaviors related to the targeted character values. Additionally, students reported increased motivation, better social relationships, and enhanced workforce readiness. This study underscores the importance of prioritizing character development in SMK education. Schools should integrate character values into all aspects of school life, equip teachers with the necessary competencies, and foster collaboration among schools, families, and the community to create a conducive environment for student character growth.